Simulation of Wind Speed Distribution Through Spreadsheets - Razzak, Atteeq; Tufail, Muhammad Yousuf; Tahir , Adeel; Adeel, Muhammad (Universitas Negeri Semarang, 2025)
A simulator was developed using a spreadsheet to model wind energy distribution, providing an accessible platform for both students and researchers. This tool aims to demonstrate the application of statistical modelling in renewable energy, using the Weibull distribution with adjustable shape and scale parameters. The simulation includes a user-friendly interface with a single spin button, enabling users to calculate probability density function (PDF) values and generate histograms to visualize the simulated PDF. The methodology involved designing an intuitive, spreadsheet-based tool that facilitates hands-on learning and modelling of wind energy systems. The results show that the simulator accurately models wind energy distribution and can be adapted to simulate other physical systems, offering flexibility for a range of research applications. This tool is especially valuable for educational purposes, providing practical experience for novice learners and enabling more advanced research for experienced researchers. The study contributes to the field by offering an accessible and effective simulation tool for wind energy modelling, enhancing the learning and research experience.